STUDY OF THE INFLUENCE OF LOW TEMPERATURES ON MATERIALS WITH A SPECIAL PURPOSE POLYMER COATING UNDER STATIC CONDITIONS - MIHAILOVA, Nina; PRIVALA, Valerii; LUSHCHEVSKA, Olena (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The domestic chemical industry urgently needs the creation of special high-class protective clothing that would allow working in extreme conditions without endangering the life and health of employees. In previous publications, it was determined that the necessary comprehensive protection against the effects of harmful production factors is provided by the creation and use of an insulating suit, which should become a barrier that prevents the penetration, and therefore the influence of mineral acids, alkalis, ammonia, salt solutions, etc. of different concentrations. That is, it is about the creation of special clothing with the required level of protection and preservation of such basic protective indicators as chemical resistance and impermeability of the material while preserving the tightness of the product as a whole. Equipment for preparation and locksmiths for cleaning closed containers for transportation and storage of aggressive environments can simultaneously be exposed not only to mineral acids, alkalis, salt solutions based on them, but also to the remains of liquid ammonia, the evaporation of which occurs when temperatures drop, which leads to primary destruction polymer coating materials for special suits. For example, local destruction in contact with liquid ammonia leads to a sharp cooling (up to - 340C) of the contact surface of the material and destruction of the polymer coating, especially during operation (in dynamics), which can lead to a violation of the tightness of the protective product. Since workers have to perform a significant number of work movements while wearing an insulating suit, there was a need to investigate such an indicator as the resistance of materials to both dynamic loads and static conditions at low temperature. The research was conducted on samples of materials with a polymer coating, which belong to the class of special purpose artificial leathers of both foreign and domestic manufacturers.